Impact of economic and climate resilience on sustainable development: A cross-country analysis - Md. Bokhtiar Hasan; Mohammed Gazi Salah Uddin; Donghyun Park; Md. Sumon Ali; John Beirne (Asian Development Bank (ADB), 2025)
Economic and climate shocks inflict huge economic costs and undermine sustainable development (SD). This study is the first comprehensive attempt to empirically assess the influence of economic and climate resilience, which can mitigate those costs, on SD. Our analysis is based on a panel dataset of 31 countries from 2007 to 2021 and advanced econometric techniques, including panel-corrected standard errors, feasible generalized least squares, panel quantile regression, and local projections. We find that economic and climate resilience have significant effects on SD. Furthermore, dynamic analysis indicates that both types of resilience have persistent effects on SD and quantile analysis validates the robustness and consistency of our findings across different stages of development.
Keywords: C33; O11; Q01; Q54; 330; sustainable economic development; economic resilience; climate resilience; panel data analysis